Autism spectrum disorder: A family and community medicine approach (Research, Society and Development, 2024)
Objective: Highlight the role of the primary network in the early diagnosis of the development of ASD, especially the unpreparedness of the family and community care network for adaptive models. Methodology: An integrative bibliographic review was carried out using the following databases: National Library of Medicine (PubMed) and Scientific Electronic Library Online (SciELO). four descriptors were used to outline the research. This process included full texts published between 2014 and 2024 and written in Portuguese or English. The selected articles were screened considering their suitability to the topic and the following steps: (I) reading the titles, (II) the abstracts and, finally, (III) the full texts. Results: The corpus analyzed revealed that there is a correlation between the evolution of ASD and early diagnosis, inferring a tenuous role for teams of professionals and specific screening in public health. Conclusion: More advocacy and education are needed to encourage family doctors to screen for ASD, which involves more resources in the health system, from screening patients in primary care, immediate referral and an increase in immediate assessments.